Sensitivity analysis of water supply systems hydraulic models - Sousa, Ana Luís Cruz de (2022)
Nowadays, water is one of the most important assets of human society. Although the Earth’s surface is covered by 71% of water, just a small percentage of 0.0075% can be consumed. To reach the population, the drinking water must be transported from the source by the Water Supply Systems (WSS). This transportation process requires a large amount of energy, particularly with hydraulic pumps. Therefore, this process is not fully efficient, as it generally does not consider the demand for water by consumers in the different times of day and seasons of the year, nor the prices of electricity, among others. For the operational efficiency problem mentioned above, the WSS can be improved with the use of hydraulic models and optimization algorithms. This approach supports the operation and management with important details, which allows for obtaining the optimal solution. Nevertheless, the combination of hydraulic models and optimization algorithms requires an effective sensitivity analysis. This work aims to perform an expedited methodology to solve the energy-efficient operation of WSS. Thus, it is focused on the reproduction of hy draulic systems in models, to be analysed and become more efficient with a gradient-based algorithm (analytical sensitivity analysis). The analytical sensitivity analysis was compared to finite difference, and it was validated with two numerical case studies, a simple network and the AnyTown Modified benchmark. As expected, the results show that the analytical sensitivities have more accurate results than the finite difference method, as well as need fewer computational resources. This supports the advantage of using this analytical methodology to replace what is in use by the hydraulic simulators, namely the finite difference method.